Вынести общий знаменатель за скобки 1)a^k+2 - a^k 2)x^p+2 - x^p+1 3)x^p+3 - x^p+1 3)b^n-3 - b^n - b^n-2

Bihan231 Bihan231    3   02.07.2019 21:30    0

Ответы
EnderDragon500 EnderDragon500  26.07.2020 23:32
Решение
1)a^(k+2) - a^k = [(a^)*a²] - a^k = (a^k)*(a² - 1)
2)x^(p+2) - x^(p+1) = [(x^p)*x² - (x^p)*x] = [x* (x^p)]*(x - 1)
3)x^(p+3) - x^(p+1) = [(x^p)*x³ - (x^p)*x] = [x*(x^p)]*(x² - 1)
3)b^(n-3) - b^n - b(n-2) = (b^n)*b⁻³ - (b^n) - ( b^n)*b⁻² = 
= (b^n)*(1/b³ - 1 - 1/b²)
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика